PENGARUH UKURAN PERUSAHAAN, LEVERAGE, RISIKO SISTEMATIK, DAN INVESTMENT OPPORTUNITY SET TERHADAP EARNINGS RESPONSE COEFFICIENT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2012-2014 - Sufiyati, Ivan Kurnia, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
The purpose of this research is to gain empirical evidence about the influence of firm size, leverage, systematic risk, and investment opportunity set on earnings response coefficient on manufacturing companies listed in Indonesia Stock Exchange for 2012-2014. Samples selected by using purposive sampling method. This research used a sample of one hundred fourty one manufacturing companies. The result of this research indicate that only systematic risk have an influence on earnings response coefficient while firm size, leverage, and investment opportunity set has not an influence on earnings response coefficient. For a better results, further research may add another variable that influence on earnings response coefficient.